2020
DOI: 10.1002/pbc.28627
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response of CNS high‐grade neuroepithelial tumors with MN1 alteration

Abstract: Central nervous system high-grade neuroepithelial tumor with MN1 alteration (CNS HGNET-MN1) is a rare recently described entity. Fourteen CNS HGNET-MN1 patients were identified using genome-wide methylation arrays/RT-PCR across seven institutions. All patients had surgery (gross total resection: 10; subtotal resection: four) as initial management followed by observation alone in three patients, followed by radiotherapy in eight patients (focal: five; craniospinal: two; CyberKnife: one) and systemic chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Moreover, in astroblastoma or neuroepithelial tumors, patients with MN1 rearrangement were reported to have longer survival and better prognosis ( 65 , 68 ). However, some researchers considered no significant superiority in the clinical progression and prognosis of these patients ( 69 ). So far, it is unknown with respect to the relationship between the expression of MN1 at the transcriptome level and the prognosis of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in astroblastoma or neuroepithelial tumors, patients with MN1 rearrangement were reported to have longer survival and better prognosis ( 65 , 68 ). However, some researchers considered no significant superiority in the clinical progression and prognosis of these patients ( 69 ). So far, it is unknown with respect to the relationship between the expression of MN1 at the transcriptome level and the prognosis of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of this vast difference in outcomes despite the unifying molecular diagnosis remain unknown and likely include clinical features, tumor genomics and treatment modalities. Table 2 also highlights a discrepancy between PFS and OS as many patients experience short PFS yet prolonged OS with some experiencing late recurrences ( 9 , 11 ). Sturm and colleagues reported that of the eight patients diagnosed with HGNET-MN1 in their study, 100% experienced an overall survival (OS) beyond 8 years, but only two had a progression-free survival (PFS) that extended beyond 6 years ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested molecular work-up of STE in AYA patients involves testing for ZFTA fusions, which can be identified via fluorescence in situ hybridization (FISH), reverse transcriptase polymerase chain reaction (RT-PCR), next generation sequencing (NGS), or nanoString ( 45 ). In the AYA population, if a ZFTA fusion is not present then alternate diagnoses such as GBM with ependymal differentiation ( 46 ), or MN1-fused or BCOR-fused neuroepithelial tumors, should be considered ( 47 , 48 ).…”
Section: Ependymomamentioning
confidence: 99%